Effect of prehatching calls of Crocodylus moreletii on the duration and number of hatchings - Mandujano-Camacho, Hernán; Hénaut, Yann L.; Crocoft, Reginald B.; Vliet, Kent (Acta Universitaria, 2019)
Different ex situ nestings of Crocodylus moreletii underwent playbacks. These varied based on the vocalization they emit, either at the beginning or at the end of the hatching process, as well as at the repetition rate (fast or slow). playbacks with a different rate of vocal repetition of a call for help of Caiman crocodilus were included. Other nestings were incubated in silence. The hatchings lasted less time and there were more group hatchings with the final vocalization playbacks of C. moreletii and C. crocodilus, both with rapid repetition rate. The nests subjected to playbacks of initial vocalization with slow repetition rate and the nests in silence took longer to hatch, and fewer group hatches occurred. The type of vocalization and the rate of vocal repetition influence on the duration of hatching and the number of individuals that hatch together.